Syncope or seizure? The diagnostic value of the EEG and hyperventilation test in transient loss of consciousness. Issue 11 (November 1991) - Hoefnagels, W A; Padberg, G W; Overweg, J; Roos, R A; van Dijk, J G; Kamphuisen, H A
Abstract : In a prospective study of consecutive patients (age 15 or over) with transient loss of consciousness 45 patients had a history of seizure and 74 patients had a history of syncope. All patients had an EEG, ECG, laboratory tests and a hyperventilation test and were followed for an average of 14.5 months. Epileptiform activity in the interictal EEG had a sensitivity of 0.40 and a specificity of 0.95 for the diagnosis of a seizure. Epileptiform activity nearly doubled the probability of a seizure in doubtful cases. If no epileptiform activity was found, this probability remained substantially the same. The hyperventilation test had a sensitivity of 0.57 and a specificity of 0.84 for the diagnosis of syncope. A positive test increased the probability of syncope half as much in doubtful cases. A negative test did not exclude syncope. Laboratory tests were not helpful except for an ECG which was helpful in elderly patients.